2011
DOI: 10.1007/s13312-012-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene wrap for thermoregulation in the preterm infant: A randomized trial

Abstract: We compared the response of temperature adaptation in preterm infants using the polyethylene wrap with and without previous drying versus the sterile preheated field. Both groups of polyethylene use achieved a mean axillary temperature of 36.5C at 30 minutes compared with 75 minutes for the group of traditional care. At 120 minutes, the incubator temperature was higher in those using preheated field, compared with infants in the polyethylene wrap with or without previous drying, (35.15C, 34.20C and 34.20C resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 9 publications
3
19
0
1
Order By: Relevance
“…13,17-20 , Smith et al, has come up with the same results as those of the current study. The mean of body temperature at the time of admission to NICU was 36.26◦C in the intervention group and 35.79◦C in the control group and this difference was statistically significant (P=0.001).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…13,17-20 , Smith et al, has come up with the same results as those of the current study. The mean of body temperature at the time of admission to NICU was 36.26◦C in the intervention group and 35.79◦C in the control group and this difference was statistically significant (P=0.001).…”
Section: Discussionsupporting
confidence: 89%
“…Newborns with gestational age of 28-30 weeks and birth weight of 1000 to 2499 gr were included in cardona et al, study. 13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While one recent study failed to show an effect of wrapping on hypothermia rates [64], others found that this approach effectively raised body temperature [65,66] and did so more quickly than radiant heaters [67,68], however did not reduce mortality [69]. …”
Section: Discussionmentioning
confidence: 99%